Effect of Karas (Aquilaria malaccensis) on Male Reproductive Organs and Sperm Quality in Adult Sprague Dawley Rats - Norahidah Zaidi; Mohd Nizam Haron; Connie Fay Komilus; Fathurrahman Lananan; Ha Hou Chew; Nadzifah Yaakub; Asmad Kari (Tropical Life Sciences Research, 2023)
Reproductive health and male fertility are closely related to dietary practices. In recent years, Malaysia has shown a lot of interest in using herbal plants as dietary supplements or in the treatment of numerous diseases. Aquilaria malaccensis, commonly known as karas or gaharu, has recently gained attention for its potential to cure many diseases due to its pharmacological properties. However, studies on its effect on male fertility and reproductive organs are very scarce. This study was conducted to determine the effect of A. malaccensis on male reproductive organs’ weight (testis, epididymis, prostate gland and seminal vesicle) and sperm quality (sperm count, sperm morphology and sperm motility) in adult Sprague Dawley rats. Twenty-four male Sprague Dawley rats were allocated into four treatment groups; Control (C: 1 mL of distilled water, n = 6), Treatment 1 (T1: 1 g A. malaccensis/kg body weight, n = 6), Treatment 2 (T2: 2 g A. malaccensis/kg body weight, n = 6) and Treatment 3 (T3: 3 g A. malaccensis/kg body weight, n = 6), respectively. Distilled water and A. malaccensis were administered by oral gavage once daily for 28 days. The rats were euthanised on Day 29 for assessment of reproductive organs’ weight and sperm quality. Result shows that weight of testis, epididymis, prostate gland, seminal vesicle and sperm motility did not differ (p > 0.05) among control and treated groups. A significant increase (p < 0.05) of sperm number (1.36 × 10??) and a decrease (p < 0.05) in percentage of the abnormal sperm (8.17%) were observed in T1 group when compared to Control group. Incremental dosage of A. malaccensis seemed to decrease number of sperm (T3: 0.78 × 10?? < T1: 1.36 × 10?? with p < 0.05) and increase percentage of abnormal sperm (T3: 18.83% > T2: 12.17% > T1: 8.17% with p < 0.05). In conclusion, the administration of either 1, 2 or 3 grams of A. malaccensis did not alter the reproductive organs’ weight and sperm motility. However, the higher concentration of A. malaccensis consumed by the rats seemed to have detrimental effects on the number and morphology of sperm.